Establishment of Self-incompatibility Gene cDNA Microarray to Identify S-genotypes of Pyrus pyrifolia - Jiang Nan; Tan Xiaofeng; Zhang Lin; Zhang Jingguo; Hu Hongju (Horticultural Plant Journal, 2015)
Based on the cDNA sequences from hyper variable (HV) regions of identified 52 S-alleles in Oriental pear cultivars, S-RNase cDNA probes were designed, and a cDNA microarray for S-RNase detections was established. Each microarray contained 240 sites from 55 cDNA probes, including all specific cDNA sequences from the HV regions of the S-alleles. Using the cDNA of pistils of tested pear cultivars as template and Cy3 fluorescently labeling primers by PCR amplification, microarray hybridization detected the S-genotype of each pear cultivar. The genotypes inferred from the cDNA microarray hybridization signals of pear cultivars such as ‘Lijiang Huangsuanli’, ‘Xiuyu’, ‘Midu Yuli’, ‘Baimianli’, and ‘Deshengxiang’ were similar to the known genotypes of all tested cultivars. The S-RNase cDNA microarrays and the oligonucleotide gene chips were then used to conduct parallel testing of 24 P. pyrifolia cultivars with unknown S-genotypes. In conclusion, the construction of cDNA microarrays has further improved the pear S-RNase detection platform.